2021
DOI: 10.48550/arxiv.2108.10948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homomorphism complexes, reconfiguration, and homotopy for directed graphs

Abstract: The neighborhood complex of a graph was introduced by LovΓ‘sz to provide topological lower bounds on chromatic number. More general homomorphism complexes of graphs were further studied by Babson and Kozlov. Such 'Hom complexes' are also related to mixings of graph colorings and other reconfiguration problems, as well as a notion of discrete homotopy for graphs. Here we initiate the detailed study of Hom complexes for directed graphs. For any pair of directed graphs 𝐺 and 𝐻 we consider the polyhedral complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…A directed analogue of A-homotopy for simple directed graphs has also been studied [22]. More recently, Dochtermann and Singh, defined several homotopy theories for directed graphs, using both cylinder and path objects [15]. Our work also extends these ideas to closure spaces.…”
Section: Introductionmentioning
confidence: 88%
“…A directed analogue of A-homotopy for simple directed graphs has also been studied [22]. More recently, Dochtermann and Singh, defined several homotopy theories for directed graphs, using both cylinder and path objects [15]. Our work also extends these ideas to closure spaces.…”
Section: Introductionmentioning
confidence: 88%
“…We are aware of two results for H-Recoloring for digraphs H. The first one is by Brewster et al, who showed that H-Recoloring admits a polynomial-time algorithm if H is a reflexive digraph cycle that does not contain a 4-cycle of algebraic girth 0 [3]. In spirit this algorithm uses the topological approach of Wrochna that reduces the task of finding H-recoloring sequences to finding vertex walks in H. Secondly, Dochterman and Singh study the Hom-complex for digraphs G and H and show that it is connected (in the topological sense) if H is a transitive tournament T n [8] on n vertices. From this they conclude that any instance of T n -Recoloring is a YES-instance and give a polynomial-time algorithm that finds a T n -recoloring sequence.…”
Section: Related Workmentioning
confidence: 99%
“…Despite several positive [1,5,7,16] and negative [2,5,13] results in this setting, a complete classification of the complexity of H-Recoloring for undirected graphs is not known. In the more general context of digraphs, we are aware of only two results for H-Recoloring, which consider the case where H is a transitive tournament [8] and where H is some orientation of a reflexive digraph cycle [3] (reflexive means that there is a loop on each vertex). We extend the topological approach of Wrochna for H-Recoloring for undirected graphs to digraphs and obtain the following results, which generalize the previous algorithmic results in [1,3,7,16].…”
Section: Introductionmentioning
confidence: 99%